Prefabrication of a skin axial flap in experiment - Stĕpán, D; Válka, J; Samohýl, J; Meyer, V E; Smahel, J (Acta chirurgiae plasticae, 1993)
Flap prefabrication was studied on the rat thigh by implanting femoral vessels into the flap's subcutaneous tissue. The aim of the experiment was to determine optimal prefabrication time, and to monitor, using contrast staining, the dynamics and morphology of the neovascularization process. The minimal time for successful prefabrication was 14 days in our experimental model. The potential of physiological and pharmacological regulation of the process of capillary neoformation is discussed. A successful attempt at free transfer of a prefabricated flap to the contralateral thigh and at femoral vessel anastomosis by microsurgery was also made as part of the experiment.
Keywords: Surgical Flaps; Rats, Wistar; Femoral Artery; Animals; potkani Wistar; patologická angiogeneze; chirurgické laloky; Female; krysa rodu Rattus; modely nemocí na zvířatech; Rats; vena femoralis; ženské pohlaví; techniky in vitro; zvířata; arteria femoralis; Femoral Vein; In Vitro Techniques; Disease Models, Animal; Neovascularization, Pathologic